IMPLICATIONS AND CONSIDERATIONS OF THE NEW ELECTRONIC INFORMATION AND TRANSACTION LAW - Purwono, Agus; M. Zamroni, M. Zamroni; Santoso, Hardi Anugrah; Miarsa, Fajar Rachmad Dwi (ANAYASA : Journal of Legal Studies, 2024)
Regarding regulations related to the electronic world, the purpose of this study is to link the law on Electronic Information and Transactions (ITE Law) No. 1 of 2024 which is the second amendment to Law No. 11 of 2008. The emergence of various problems regarding the ambiguity of protection in the scope of ITE has caused the public to urge the government to revise it as soon as possible. The methodology used in this study is normative juridical type sourced from primary and secondary legal materials. With an approach through legislation (Statute Approach) and a historical approach (Historical Approach). The Law on Information and Electronic Transactions which was born in 2008 (ITE Law No. 11 of 2008) contains provisions governing the electronic realm. Apart from that, the ITE Law has many weaknesses that conclude multiple interpretations of the contents of the article. To overcome this, the government made the first revision contained in Law No. 19 of 2016. The emergence of controversy has not been able to answer the changes in the first change. So there are still articles that reap pros and cons in the form of interpretation. Among them are Article 27, Article 28, Article 29, and Article 36. So the government made a second revision contained in Law No. 1 of 2024.